Arabidopsis IAR4 Modulates Primary Root Growth Under Salt Stress Through ROS-Mediated Modulation of Auxin Distribution - Fu, Yang; Yang, Yong; Chen, Shaoping; Ning, Nina; Hu, Honghong (Frontiers in Plant Science, 2019)
High salinity is one of the major environmental stresses that plants encounter. Roots are the initial and direct organs to perceive the signal. However, how plant roots perceive and respond to salinity at the molecular and physiological levels is still poorly understood. Here, we report that IAA-CONJUGATE-RESISTANT 4 (IAR4) plays a key role in primary root growth under salt stress conditions. Mutation of IAR4 led to increased sensitivity to salt stress conditions, with strongly inhibited primary root growth and reduced survival rate in two iar4 mutant alleles. iar4 mutants accumulated greater Na+ and exhibited a greater Na+/K+ ratio under NaCl treatment. In addition, more ROS accumulated in the iar4 mutants due to reduced ROS scavenging. NaCl treatment greatly suppressed the expression levels of ProPIN1:PIN1-GFP, ProPIN2:PIN2-GFP, ProPIN3:PIN3-GFP, and ProDR5:GFP, and suppressed root meristem activity in iar4. GSH or auxin treatment greatly recovered the PIN expressions, auxin distribution and primary root growth in the iar4 mutants, suggesting ROS is a vital mediator between salt stress and auxin response. Our data support a model in which IAR4 integrates ROS and auxin pathways to modulate primary root growth under salinity stress conditions, by regulation of PIN-mediated auxin transport.